PENGARUH PENERAPAN SELF ASSESSMENT SYSTEM, KESADARAN DAN PEMAHAMAN PERPAJAKANTERHADAP KEWAJIBAN MEMBAYAR PAJAK: Studi Empiris Pada Kantor Pelayanan Pajak Pratama Badung Utara - I Ketut Yudana Adi (Badung: LPPM Universitas Triatma Mulya, 2020)
This study discusses the Influence of Self Assessment System Implementation, Awareness and Understanding of Tax Liability on Paying Taxes On KPP Pratama Badung Utara. The data in this study was obtained from questionnaires distributed to taxpayers registered in KPP Pratama Badung Utara using probability sampling methods. Respondents were used in this study were 98 responden.Uji hypothesis is used multiple linear regression equation Y = -7.874 - 0.083X1 + 0,522X2 - 0.048X3 + é where partial awareness of taxation affect the obligation to pay taxes is indicated by the level of Sig. 0.002 <0.05, while the self-assessment system and partial understanding of taxation does not affect the obligation to pay taxes, this is indicated by the level of Sig. respectively - variable massing 0.076> 0.05 and 0.759> 0.05, but simultaneously, self-assessment system, awareness and understanding of taxation positive and significant effect on the obligation to pay taxes, this is indicated by the level Sig.0.000 <0.05.